The Use of Liposomal Bupivacaine Administered With Standard Bupivacaine in Ankle Fractures Requiring Open Reduction Internal Fixation: A Single-Blinded Randomized Controlled Trial. Issue 8 (August 2017) - Davidovitch, Roy; Goch, Abraham; Driesman, Adam; Konda, Sanjit; Pean, Christian; Egol, Kenneth
Abstract : Objectives: To determine the efficacy of liposomal bupivacaine compared to placebo for postoperative pain control in patients undergoing operative fixation of ankle fractures. Design: Prospective single-blinded randomized control trial. Setting: Academic Medical Center. Patients/Participants: After Institutional Review Board (IRB) approval, 76 patients who sustained an acute ankle fracture (OTA/AO 44A-C) requiring operative fixation met inclusion criteria. Intervention: Patients were randomly assigned to 1 of 2 groups, control (local intraoperative sterile saline injection under general anesthesia) or interventional (local intraoperative liposomal bupivacaine and bupivacaine injection under general anesthesia). Injections were administered in a standardized fashion and included injection of a 1:1 mixture of a 40 mL solution consisting of 1.3% Exparel and sterile saline (interventional) or a 40 mL injection of normal saline (control) into the surrounding periosteal, peritendinous, surrounding muscles and subcutaneous tissue of the surgical incision(s). Main Outcome Measurements: Pain medications administered and pain according to the Visual Analogue Scale was recorded at scheduled postoperative time points: 4, 24, 48, 72, and 336 hours (14 days). Results: Thirty-nine patients were randomized to the control group and 37 to the interventional group (mean age = 42 ± 15 years), with no statistically significant differences between groups with regards to severity of injury and patient demographics. Pain scores were significantly lower in the interventional group versus control up to 2 weeks after surgery. Percocet ingestion at 4 hours was significantly lower in the interventional group (0.7 vs. 1.3, P = 0.004), while it approached significance at 48 hours postoperatively (2.8 vs. 3.69, P = 0.07). No other significant differences were noted for Percocet ingestion postoperatively at other time points assessed. The overall satisfaction with pain control was not statistically different between the 2 groups ( P = 0.93). Conclusion: Local intraoperative infiltration of liposomal bupivacaine administered with standard bupivacaine for ankle fractures requiring Open Reduction Internal Fixation (ORIF) affords improved pain relief in the immediate postoperative period resulting in a reduction in Percocet ingestion, with resultant effects seen up to 2 days postoperatively. Continued investigation of this drug for use with extremity fractures is warranted. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.